2022
DOI: 10.1101/2022.12.01.518661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Viability of HepG2 and MCF-7 Cells is not Correlated with Mitochondrial Bioenergetics

Abstract: Alterations in metabolism is a hallmark of cancer. It is unclear, however, if oxidative phosphorylation (OXPHOS) is required for tumor cell survival. We investigated the effect of severe hypoxia, site-specific inhibition of respiratory chain (RC) components, and uncouplers on the survival of HepG2 and MCF-7 2D cultured cells. Comparable respiratory complex activities were observed in both cell lines, but HepG2 cells exhibited much higher oxygen consumption rates (OCR) and respiratory capacity than the MCF-7 ce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Our data support these findings and show for the first time that glutamine could be fermented for sufficient ATP content in glioma cells. Also consistent with recent findings in non-neural tumors (Doczi et al, 2023), our data show that ATP contribution through OxPhos was neither necessary nor sufficient for the growth of the VM-M3, CT-2A, or U-87MG glioma cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data support these findings and show for the first time that glutamine could be fermented for sufficient ATP content in glioma cells. Also consistent with recent findings in non-neural tumors (Doczi et al, 2023), our data show that ATP contribution through OxPhos was neither necessary nor sufficient for the growth of the VM-M3, CT-2A, or U-87MG glioma cells.…”
Section: Discussionsupporting
confidence: 90%
“…We found that VM-M3 cells were more sensitive to inhibition of glutamine catabolism upstream of succinyl-CoA synthetase using the alpha-ketoglutarate dehydrogenase inhibitor sodium arsenite than from inhibition of complex IV using potassium cyanide. In addition to maintaining oxygen-independent ATP content for glioma cell viability, ATP production through glutamine-driven mSLP can also reduce ATP hydrolysis from a reversal of the ATP synthase reaction during bioenergetic stress (Chinopoulos et al, 2010; Doczi et al, 2023; Ravasz et al, 2024). Our results suggest that glutamine, which has been considered primarily an anaplerotic respiratory fuel for growth, can also be fermented via mSLP, as an energy mechanism that has been largely unrecognized in cancer, especially in gliomas (Wise and Thompson, 2010; Martins et al, 2020; Garcia et al, 2021; Khadka et al, 2021; Ravasz et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the methods used to evaluate cell death in the present study may not have been as sensitive as those used in previous studies (45,48). Of note, the study by Doczi et al (63) demonstrated that the viability of HepG2 cells was not decreased by the complete inhibition of mitochondrial respiration. Nonetheless, in agreement with the study by Amorim et al (15), the FFA-treated HepG2 cells exhibited compensatory mitochondrial proliferation marked by the increased expression of the PPARGC1A gene and citrate synthase activity, secondary to excessive mitochondrial damage.…”
Section: Discussionmentioning
confidence: 97%
“…This result is consistent with recent findings indicating that cell viability could not be correlated with mitochondrial bioenergetics. 46 Antibacterial Activity of SF-C n -TPP. Like other zwitterionic uncouplers, 35,39,47 SF-C n -TPP (n = 4, 5, 10) exhibited antibacterial activity with Gram-positive species.…”
Section: Direct Measurements Of Proton Transport Induction By Sf-c N ...mentioning
confidence: 99%